Germination Behaviour and Biochemical Contents of Quercus glauca Thunb. Acorns in Relation to Pre-Sowing Treatments and Acorn Sizes - Amare, T.; Bhardwaj, D. R. (Indian Forester, 2017)
Like many other oak species in the Himalayas Quercus glauca forests are facing sever degradation and regeneration problem which calls for forest restoration and supplementary planting program. Understanding germination behavior of the species is crucial to meet the demand of better quality seedlings in the required amount. The current study examined the effect of seven pre-sowing seed treatments and three acorn sizes on germination traits and biochemical content of Q. glauca acorns. The results suggested that all pre-sowing treatments had better germination performance than the control while application of GA at the concentration of 100 ppm had the best germination traits. The concentration of Soluble 3 protein, starch and total sugar of treated acorns was closely related to germination per cent of those treatments in which these biochemical contents decreased with increasing germination per cents. Total phenol content was closely related to moisture content of treated acorns, as it decreased with increase in moisture content. Likewise, acorn size had significantly affected germination traits and biochemical contents of treated acorns. Bigger sized acorns had superior performance in germination and biochemical contents than medium and small sized ones. The study concluded the application of GA as 3 pre-sowing treatment and the use of bigger sized acorns to enhance germination per cent.